PEMETAAN MAAR DAN CINDER CONE WILAYAH GUNUNG LAMONGAN MENGGUNAKAN ANALISIS POWER SPECTRUMDAN UPWARD CONTINUATION - Supriyadi Supriyadi; Toviatun Toviatun; Agus Suprianto (Universitas Sriwijaya, 2020)
The gravity method is a method often used in geophysical exploration. According to recent technological developments, data acquisition has evolved by utilizing satellite data and modeling, one of which is GGMplus gravity data. In this study, GGMplus gravity data will be used to map the distribution of maar and cinder cones in the Gunung Lamongan Region. To obtain the optimal local anomaly results of gravity data, a combination of power spectrum analysis and upward continuation filtering methods is carried out.ABL data contours are sliced, gravity anomaly data from each slicing path is processed using FFT so that the wave number and power spectrum values are obtained as well as the relationship graph between the two.The power spectrum analysis method provides window width data that is used as information on determining the height of the upward continuation method.The ABL contour map in the Gunung Lamongan region shows a range of gravitational field values between -20 mGal to 50 mGal. High anomaly values indicate the existence of Mount Lamongan which is dominated by intrusive rocks. The subsurface structure of the Gunung Lamongan region is thought to consist of tuff, lava, volcanic breccia, and lava. The existence of maar and cinder cones in the Gunung Lamongan area can be mapped from the contours of the local anomaly. Local anomaly contours are obtained from ABL data by connecting the two methods of filtering i.e power spectrum analysis and upward continuation. There are 10 cinder cones and 8 maar visible on the local anomaly contour map.